2014
DOI: 10.1107/s1399004714014278
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into arginine methylation by the mouse protein arginine methyltransferase 7: a zinc finger freezes the mimic of the dimeric state into a single active site

Abstract: Protein arginine methyltransferase 7 (PRMT7) is a type III arginine methyltransferase which has been implicated in several biological processes such as transcriptional regulation, DNA damage repair, RNA splicing, cell differentiation and metastasis. PRMT7 is a unique but less characterized member of the family of PRMTs. The crystal structure of full-length PRMT7 from Mus musculus refined at 1.7 Å resolution is described. The PRMT7 structure is composed of two catalytic modules in tandem forming a pseudo-dimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 76 publications
1
63
0
Order By: Relevance
“…S1) as well as previous small-angle X-ray scattering studies (13) showed that TbPRMT7 forms a homodimer in solution. The juxtaposition of the two tandem PRMT cores in mouse and roundworm PRMT7 crystal structures recapitulates the dimeric TbPRMT7 architecture, sharing a similar overall quaternary structure (19,20). Although only one PRMT module is catalytically active in mouse PRMT7 (MmPRMT7) and roundworm PRMT7 (CePRMT7) (19,20), our data (Table 1), as well as those of others, suggest that dimerization of PRMT7 cores-either by a noncovalent assembly or by juxtaposition of two units as part of one polypeptide-is a prerequisite for catalytic activity (19,20).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…S1) as well as previous small-angle X-ray scattering studies (13) showed that TbPRMT7 forms a homodimer in solution. The juxtaposition of the two tandem PRMT cores in mouse and roundworm PRMT7 crystal structures recapitulates the dimeric TbPRMT7 architecture, sharing a similar overall quaternary structure (19,20). Although only one PRMT module is catalytically active in mouse PRMT7 (MmPRMT7) and roundworm PRMT7 (CePRMT7) (19,20), our data (Table 1), as well as those of others, suggest that dimerization of PRMT7 cores-either by a noncovalent assembly or by juxtaposition of two units as part of one polypeptide-is a prerequisite for catalytic activity (19,20).…”
Section: Discussionmentioning
confidence: 72%
“…Notably, TbPRMT7 and mammalian PRMT7 have a distinct structural organization (9,10,13,20). Although the mammalian enzymes contain two PRMT cores in tandem, the trypanosomal enzyme contains only one PRMT core.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the different PRMTs vary significantly in overall size and sequence, they share a common active site architecture defined by specific amino acids (belonging to the so-called motifs I to IV) known to be key for catalysis (Fig. 1A) (1)(2)(3)(4)12). Most notable in this regard are residues involved in hydrogen bonding to the adenosine moiety of AdoMet and two conserved glutamate residues that form the so-called "double-E loop" critical for chelating and orienting the guanidine group of the target arginine residue.…”
mentioning
confidence: 99%